Association between brachial-ankle pulse wave velocity and risk of type 2 diabetes mellitus: results from a cohort study. Issue 1 (21st July 2020) - Lou, Yan-mei; Liao, Min-qi; Wang, Chang-yi; Chen, Hong-en; Peng, Xiao-lin; Zhao, Dan; Gao, Xu-ping; Xu, Shan; Wang, Li; Ma, Jian-ping; Ping, Zhao; Zeng, Fang-fang
Abstract : Introduction: Brachial-ankle pulse wave velocity (ba-PWV), as a simple and easily measured marker of arterial stiffness, has not been prospectively explored for its role in type 2 diabetes mellitus (T2DM) risk among the general population. This study aimed to explore the association between baseline ba-PWV value and new-onset T2DM among Chinese adults. Research design and methods: Using data from Xiaotangshan Hospital, we conducted a prospective cohort study among those who underwent annual or biennial health check-up examinations and who had their ba-PWV measured from 2009 to 2016. We explored the risk of new-onset T2DM across ba-PWV tertiles using Cox proportional-hazards regression analysis. Results: Of 6122 adults (68.9% male; mean age: 51.0 (SD 13.0) years) without T2DM and with ba-PWV measured at baseline, 599 participants developed T2DM during an average of 3.8 (SD 2.3) years of follow-up. After multivariable adjustment, ba-PWV was positively related to T2DM risk (p for trend=0.008). Compared with the lowest ba-PWV tertile, the HRs and their 95% CIs were 1.57 (1.18 to 2.10) for the second and 1.66 (1.24 to 2.22) for the third tertile. The risk across ba-PWV tertiles increased steadily from 1000 cm/s to 1400 cm/s and then reached a plateau. Subgroup analyses indicated a significantly higher risk among those aged <65 years and current smokers (p for interactions: <0.001 and 0.006). Conclusions: Our findings suggest that ba-PWV might be a useful and independent predictor of new-onset T2DM with ba-PWV ranging between 1000 cm/s and 1400 cm/s, especially among younger individuals and current smokers.